Análisis comparativo de las demandas físicas de dos tareas de juego reducido en fútbol profesional - Nevado-Garrosa, F.; Tejero-González, C. M.; Paredes-Hernández, V.; del Campo-Vecino, J. (Archivos de medicina del deporte, 2015)
The aim of the present study was to compare the physical demands of two SSG (small sided games) modifying the relative pitch area per player. The study followed a pre-experimental design only group. A total often professional soccer players belonging to a team of Spanish first division soccer league were monitored during two diff erent SSG: 7x7 (25x45 m) and 11x11 (60x45 m). Using GPS the following cinematic variables were measured: distance, distance at high speed running, number of moderate accelerations, average number of accelerations, number of maximal acceleration, duration of acceleration, and distance traveled during acceleration. After checking the normal distribution, data were analyzed by T test for related sample, and eff ect size was estimated using percentage change. According to the results, in 11x11 SSG players covered more total distance (p = 0.003), covered more distance at high intensity running (p = 0.016) and accelerations occurred along more time (p = 0.017) and distance (p = 0.001). In the 7x7 SSG more number of moderate (p = 0.002) and medium (p = 0.004) accelerations were registered. Even though the total workload is higher in the 11x11 situation, 7x7 is more demanding in terms of accelerations and direction changes, which implies a diff erent internal load, more neuromuscular. Furthermore, the physical demands of the SSG 7x7, where a higher number of accelerations are performed, becoming the 7x7 an ideal task to work specifi c strength, in a context where physical, technical and tactical aspects are integrated.